Impact assessment of IFPRI’s capacity-strengthening work, 1985–2010 - Kuyvenhoven, Arie (International Food Policy Research Institute, 2014)
Strengthening national capacities for undertaking, communicating, and using evidence-based food policy analysis has long been one of the International Food Policy Research Institute’s (IFPRI’s) major objectives. To that end, IFPRI has engaged in different kinds of capacity strengthening that include formal training, (policy) networks, country strategic policy support, research collaboration with individuals and organizations, institutional development, support to university degree programs, visiting fellows, and training of postdoctoral fellows (PDFs).